2006
DOI: 10.1094/ats-2006-0502-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Triclopyr Safens the Use of Fluazifop and Fenoxaprop on Zoysiagrass While Maintaining Bermudagrass Suppression

Abstract: Three sequential applications of fenoxaprop (1.0 lb/acre), fluazifop (0.09 lb/acre), fluroxypyr (0.23 lb/acre), and triclopyr (0.12 lb/acre) applied on 28‐day intervals were evaluated alone and in various combinations for bermudagrass suppression in zoysiagrass turf. Triclopyr safened the use of fenoxaprop and fluazifop on zoysiagrass turf without decreasing bermudagrass suppression compared to fenoxaprop or fluazifop alone. The addition of triclopyr improved fenoxaprop suppression of bermudagrass over fenoxap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 5 publications
5
49
1
Order By: Relevance
“…For example, triclopyr is only labeled for cool-season grasses and zoysiagrass (Zoysia japonica Steud.) because of excessive injury potential from labeled use rates (0.28 to 1.12 kg ha −1 ) on most warm-season species during active growth (Cudney et al 1997;McElroy and Breeden 2006). Glyphosate was less efficacious than triclopyr at rates evaluated and would be limited to spot applications for POST control of spotted spurge.…”
Section: Resultsmentioning
confidence: 99%
“…For example, triclopyr is only labeled for cool-season grasses and zoysiagrass (Zoysia japonica Steud.) because of excessive injury potential from labeled use rates (0.28 to 1.12 kg ha −1 ) on most warm-season species during active growth (Cudney et al 1997;McElroy and Breeden 2006). Glyphosate was less efficacious than triclopyr at rates evaluated and would be limited to spot applications for POST control of spotted spurge.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned previously, bermudagrass is an invasive weed of seashore paspalum that is difficult to control once established. Herbicides commonly used to suppress or control bermudagrass include fluazifop, triclopyr, siduron, and ethofumesate (14,18,19). In the present study, all caused severe injury to seashore paspalum seedlings and do not appear to be viable options for use in controlling bermudagrass in seashore paspalum seedlings.…”
Section: Herbicide Injury On Seedling Sea Spray Seashore Paspalummentioning
confidence: 99%
“…On the following evaluations, there was no evolution of symptoms, which consisted of bleached leaves, and plants continued to grow and, at 42 DAA, no more signs of the initial symptoms were observed. McElroy and Breeden (2006) ) show the injuries were of 10% or bellow. Similar results were obtained by Lewis et al (2012).…”
Section: Itg5 -Imperial Grassmentioning
confidence: 95%
“…Some papers show triclopyr toxicity effect upon Cynodon species. McElroy and Breeden (2006) evaluating its effect at 1.23 kg a.e.ha clopyralid reducing soil cover about 56%, at 21 DAA and, these injuries were associated mainly by the herbicide triclopyr. Johnson and Duncan (2001) found that applications of triclopyr cause injuries around to 30% at 2 DAA.…”
Section: Bermuda Grassmentioning
confidence: 99%